Nelson essentials of pediatrics (S. W. Saunder Co., 1990)
The Third Edition of this resource features a review of all the common and uncommon disorders in children. It distils the outstanding features of the bestselling Nelson Textbook of Pediatrics, 15th Edition into a clinically-orientated reference.